Case Report: Successful treatment with methotrexate in a 10-year-old boy with co-occurrence of generalized psoriasis and vitiligo - Leong, Pui-Ying; Chiu, Tsu-Man; Wei, James Cheng-Chung; Huo, An-Ping (Frontiers in Immunology, 2023)
Psoriasis (PsO) and vitiligo co-occurrence are rare in Asian countries, especially for children. This case report presents the first-ever occurrence of PsO combined with vitiligo in an Asian boy under six who achieved successful symptom improvement using methotrexate (MTX) as the sole treatment. Although previous studies indicated a close correlation between the two diseases, using MTX, a common treatment for PsO, is not a standard treatment for vitiligo. Even with advanced progress in biologics and Janus kinase inhibitor (JAKi), the biologics and JAKi used in vitiligo are still inconsistent. In our case, the successful use of MTX implies the shared immune pathways between PsO and vitiligo. Further exploration is needed to optimize treatment options for this co-occurrence of PsO and vitiligo.